Smart Libraries as Mediators: Linking Learning University Library Models to Organizational Performance - Min, Deng; Wongvanichtawee, Chalermkiat (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: In the era of smart transformation, this study examines the impact of the learning university library model on university library performance, with the smart library serving as a mediator. Materials and Methods: Drawing on theories of smart libraries, learning organizations, and organizational performance, the research focuses on leaders and department heads of university libraries in Guangxi. A questionnaire survey conducted in 2024 yielded 437 valid responses. Utilizing statistical software, the study constructed a structural equation model (SEM) for analysis. Results: The findings revealed that the smart library served as a key mediator, significantly enhancing the positive influence of the learning university library model on university library performance (standardized path coefficientβ= 0.261, p < 0.001). Learning (β= 0.229，p < 0.001) and technology (β = 0.225，p < 0.001) emerged as primary drivers of performance improvement, while resource, personnel, and organizational factors also played crucial roles. Conclusion: This study contributes to interdisciplinary scholarship on smart libraries and learning organizations while offering actionable strategies for optimizing library performance and sustainable development in Guangxi and similar contexts. Despite its contributions, limitations include regional bias (Guangxi-focused sample) and reliance on self-reported data.